Pediatric cat-scratch disease: An illness hidden among lymphadenitis (Indian Journal of Case Reports, 2025)
Cat-scratch disease (CSD) is a self-limiting disease caused by Bartonella henselae. Its diagnosis requires a thorough history of scratch or bite, clinical examination of the primary rash before the onset of lymphadenitis, investigations, such as Bartonella antibody titers, and a wait-and-watch policy. Azithromycin 10 mg/kg day 1 and 5 mg/kg day 2–4 or the adult dose is recommended to treat this case. An 11-year-old boy presents with a multiple, papular, approximately 0.5 by 0.5 cm, non-pruritic, non-erythematous rash over the nape of the neck of 3 weeks, bilateral swollen cervical lymph nodes of which the largest lymph node (Bubo) on the left side of approximately 3–5 cm in the horizontal dimension of 2 weeks. Bartonella antibody panels came positive with B. henselae of immunoglobulin G titers of 1:2048. Oral azithromycin helped resolve the rash and caused a 50% reduction of the bubo by 48 h. The bubo became less prominent with treatment and observation was continued for 6 months. CSD should be considered as a differential diagnosis by physicians. The primary rash before the onset of Bubo is the signature that heralds the diagnosis of CSD. The pediatrician must investigate only if there is a strong correlation with a scratch/bite from a cat or dog.